Electrochemical studies based on local interfacial ph changes of gold nanoparticles immobilized on polystyrene brushes - Antonio, Tamara R.T.A. [UNESP]; Basso, Caroline R. [UNESP]; Cabra, Murilo F.; Pedrosa, Valber A. [UNESP] (My University, 2013)
The electrochemical behavior of polystyrene modified with gold nanoparticle (Au NPs) was investigated in terms of pH-responsive polymer brush. A pH-responsive of modified polymer brush from tethered polystyrene was prepared and used for selective gating transport of anions andcations across the thin-film. An ITO-coated glass electrode was used as substrate and applied to study the switchable permeability of the polymer brush triggered by changes in pH of the aqueous environment. The pH-sensitive behavior of the polymer brush interface has been demonstrated by means of cyclic voltammetry (CV) and Localized Surface Plasmon Resonance (LSPR). CV experiments showed at ph values of 4 and 8 induces swelling and shrinking of the grafted polymer brushes, respectively, and this behavior is fast and reversible. LSPR measurements showed a blue shift of 33 nm in the surface resonance band changes by local pH. The paper brings an easy methodology to fabrication a variety of nanosensors based on the polymer brushes-nanoparticle assemblies. © 2013 by ESG.
Keywords: Gold nanoparticle; Local pH change; Polymer brushes; Stimuli-responsive materials